Silver nanowire transparent conductive film preparation method combining semi-curing and low-pressure pressing

By combining semi-curing and low-voltage mechanical pressing, the Ag-NW transparent conductive film was prepared, which solved the problems of poor adhesion and high surface roughness, and achieved the effects of high adhesion, low surface roughness, excellent mechanical flexibility and photoelectric properties.

CN119763928APending Publication Date: 2025-04-04Wenzhou University Carbon Materials and Hydrogen Energy Industry Technology Research Institute +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411964441.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing Ag-NW transparent conductive films face problems of poor adhesion and high surface roughness in applications, resulting in degraded conductivity and interlayer short circuits of optoelectronic devices.

Method used

An Ag-NW transparent conductive film was prepared by combining semi-curing and low-pressure mechanical pressing. A mixed solution of polymer and crosslinking agent was coated on the PET substrate to form a semi-cured bonding layer, and then a silver nanowire dispersion was coated on the surface, and a low-pressure pressing and complete curing treatment was carried out.

Benefits of technology

The adhesion of the Ag-NW transparent conductive film is improved and its surface roughness is reduced, its mechanical flexibility and photoelectric properties are enhanced, and the problems of poor adhesion and high surface roughness are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763928A_ABST
    Figure CN119763928A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a silver nanowire transparent conductive film combining semi-curing and low-pressure pressing, which comprises the following steps: coating the surface of a PET (Polyethylene Terephthalate) base material with 200-300 mu L of a mixed solution of a polymer and a cross-linking agent, and carrying out first heating treatment to obtain a semi-curing bonding layer taking PET as a substrate; coating 100-1000 [mu] L of AgNW dispersion liquid with the concentration of 0.2-1.0 mg / mL on the surface of the semi-cured bonding layer, and performing drying treatment to obtain the transparent conductive film with the semi-cured bonding layer as the substrate; placing a pressure piece on the transparent conductive film to press the transparent conductive film; carrying out second heating treatment on the pressed transparent conductive film to obtain a transparent conductive film taking the completely cured bonding layer as a substrate; the prepared Ag-NW transparent conductive film has the advantages of high adhesive force, low surface roughness, excellent mechanical flexibility and photoelectric property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of preparation of transparent conductive films, and more specifically to a method for preparing a silver nanowire transparent conductive film with high adhesion and low surface roughness by combining semi-curing and low-pressure mechanical pressing. Background Art

[0002] Transparent conductive films based on indium tin oxide (ITO) dominate commercial applications, but due to the poor mechanical properties of ITO (resistance increases significantly after slight folding or bending), high production costs and shortage of indium oxide resources, ITO can no longer meet the development direction of wearable, foldable and low-cost electronic devices. In view of this, high molecular conductive polymers, carbon nanotubes, graphene, metal grids and metal nanowires have been widely studied to replace ITO materials. Among these studied materials, one-dimensional silver nanowires (AgNW) have become a good choice for making flexible transparent conductive film materials due to their advantages such as bending resistance, high light transmittance, good electrical and thermal conductivity.

[0003] In order to meet the development needs of electronic devices, Ag-NW transparent conductive films should have high conductivity, high transmittance, high adhesion, low surface roughness and excellent mechanical flexibility. So far, researchers have explored and implemented a variety of strategies, such as plasma welding, thermal annealing, nanowire assembly and Mxene and Ag-NW composite films, which have significantly improved the performance of Ag-NW transparent conductive films in terms of conductivity and transmittance. Despite this, Ag-NW transparent conductive films still face the problems of poor adhesion and high surface roughness in practical applications. The poor adhesion between AgNW and the substrate will directly cause the Ag-NW transparent conductive film to fall off from the substrate surface when it undergoes repeated bending, stretching or slight scratching and squeezing during device assembly, thereby causing an increase in surface resistance and a decrease in conductive performance; in addition, the large roughness of the surface of the Ag-NW transparent conductive film will also cause interlayer short circuits in optoelectronic devices and large leakage currents. Summary of the invention

[0004] The purpose of the present application is to provide a method for preparing a silver nanowire transparent conductive film with high adhesion and low surface roughness by combining semi-curing and low-pressure mechanical pressing, so as to improve the adhesion of the silver nanowire transparent conductive film and reduce its surface roughness.

[0005] In order to achieve the above-mentioned purpose, the present application provides, on the one hand, a method for preparing a silver nanowire transparent conductive film combined with semi-curing and low-pressure pressing, comprising: coating 200-300 μL of a mixed solution of a polymer and a cross-linking agent on the surface of a polyethylene terephthalate (PET) substrate, and obtaining a semi-cured adhesive layer with PET as the base after a first heating treatment; coating 100-1000 μL of a silver nanowire (AgNW) dispersion with a concentration of 0.2-1.0 mg / mL on the surface of the semi-cured adhesive layer, and obtaining a transparent conductive film with the semi-cured adhesive layer as the base after a drying treatment; placing a pressure piece on the transparent conductive film to perform a pressing treatment on the transparent conductive film; and performing a second heating treatment on the pressed transparent conductive film to obtain a transparent conductive film with a fully cured adhesive layer as the base.

[0006] Preferably, the polymer is one of polydimethylsiloxane, polyvinyl alcohol, chitosan or sodium alginate.

[0007] Preferably, the mixed solution comprises: a polymer and a cross-linking agent are mixed in a ratio of 10:1.

[0008] Preferably, coating the mixed solution on the surface of the PET substrate comprises: coating by one of spin coating, Mayer rod coating or extrusion coating.

[0009] Preferably, the spin coating includes: the rotation speed is set to 1000 r / min, and the time is set to 30 seconds.

[0010] Preferably, coating the AgNW dispersion on the surface of the semi-cured bonding layer comprises: coating by one of spin coating, Mayer rod coating or extrusion coating.

[0011] Preferably, the first heating treatment includes: the heating temperature is set to 70° C., and the heating time is set to 5 minutes.

[0012] Preferably, the solvent of the AgNW dispersion is one of ethanol, water or propanol.

[0013] Preferably, the pressing process includes: the pressing pressure is set to 0.4N-0.6N.

[0014] Preferably, the second heating treatment includes: the heating temperature is set to 70° C., and the heating time is set to 4 hours.

[0015] This application can achieve the following beneficial effects: 1. This application adopts a method combining semi-curing and low-pressure mechanical pressing to prepare a silver nanowire (Ag-NW) transparent conductive film. The semi-cured polydimethylsiloxane (PDMS) layer does not have the fluidity of liquid but still retains its inherent adhesiveness. The lack of fluidity reduces the probability of PDMS flowing into the contact points between nanowires (NW-NW) during the embedding process of AgNW. Compared with the traditional embedding scheme, the semi-cured adhesive layer improves the adhesion between AgNW and the substrate, reduces the surface roughness, and gives the Ag-NW transparent conductive film excellent photoelectric properties; on the other hand, the adhesion of the Ag-NW transparent conductive film after low-pressure mechanical pressing and complete curing is further improved, and the surface roughness is further reduced. A Ag-NW transparent conductive film with high adhesion, low surface roughness, excellent mechanical flexibility and photoelectric properties is successfully prepared.

[0016] 2. This application is simple, effective and fast and can be operated in an atmospheric environment.

[0017] 3. The Ag-NW transparent conductive film prepared in this application has high adhesion, low surface roughness, excellent mechanical flexibility and optoelectronic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0019] Figure 1 It is a schematic diagram of the preparation process of PET / AgNW, PET / S-PDMS / AgNW and P-PET / S-PDMS / AgNW transparent conductive films provided in the embodiments of the present application; Figure 2 It is a schematic diagram of the effect of the liquid and semi-cured PDMS bonding layers on the Ag-NW contact resistance provided in the embodiments of the present application; Figure 3 It is a comparative schematic diagram of the effects of the liquid and semi-cured PDMS adhesive layers provided in the embodiments of the present application on the photoelectric properties of the Ag-NW transparent conductive film; Figure 4 Schematic diagram of evaluating the adhesion of the Ag-NW transparent conductive film provided in the embodiment of the present application; Figure 5 Schematic diagram of AFM characterization of the surface roughness of the Ag-NW transparent conductive film provided in the embodiment of the present application; Figure 6It is a schematic diagram of evaluating the mechanical flexibility of the Ag-NW transparent conductive film provided in the embodiment of the present application. DETAILED DESCRIPTION

[0020] Hereinafter, embodiments will be described with reference to the drawings.

[0021] It should be noted that the disclosed content is only an example, and the invention is not limited by the content described in the following embodiments. Deformations that are easy for a person skilled in the art to think of are of course included in the scope of the disclosure. In order to make the description clearer, in the drawings, there are also cases where the size, shape, etc. of each part are changed relative to the actual implementation form and schematically represented. In multiple drawings, there are also cases where the same reference numerals are marked on corresponding elements and detailed descriptions are omitted.

[0022] In the description of the following specific embodiments of the present application, AgNW refers to silver nanowires, and Ag-NW refers to related additional components of silver nanowires, such as Ag-NW transparent conductive films.

[0023] Example 1 This embodiment provides a method for preparing a Ag-NW transparent conductive film with high adhesion and low surface roughness by combining semi-curing and low-pressure mechanical pressing, including the following preparation steps: S1: 300 μL of a mixed solution of a polymer and a cross-linking agent was coated on the surface of a polyethylene terephthalate (PET) substrate, and heated at 70° C. for 5 minutes to obtain a semi-cured adhesive layer based on PET.

[0024] The above S1 is a preparation step of a semi-cured adhesive layer. Specifically, the polymer can be polydimethylsiloxane (PDMS), and the PDMS and the cross-linking agent are mixed in a ratio of 10:1 to obtain a PDMS solution. 300 μL of the PDMS solution is taken, and the coating method can be spin coating. The 300 μL PDMS solution is spin-coated on the surface of the PET substrate at 1000 r / min for 30 seconds, and the substrate is heated at 70°C for 5 min to obtain a semi-cured adhesive layer based on PET. The semi-cured PDMS layer does not have the fluidity of liquid but still retains its inherent adhesion.

[0025] It is conceivable that the polymer may also be selected from vinyl alcohol, chitosan or sodium alginate.

[0026] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0027] S2: coating 100 μL of a silver nanowire (AgNW) dispersion having a concentration of 0.8 mg / mL on the surface of the semi-cured adhesive layer, and obtaining a transparent conductive film with the semi-cured adhesive layer as a substrate after drying; The above S2 is the coating of AgNW transparent conductive film. Specifically, the solvent of AgNW dispersion can be ethanol. 100 μL of AgNW ethanol dispersion with a concentration of 0.8 mg / mL is coated on the semi-cured adhesive layer prepared in S1 four times and then allowed to dry naturally.

[0028] It is conceivable that the solvent of the AgNW dispersion may also be water or propanol.

[0029] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0030] S3: placing a pressure piece on the transparent conductive film to perform a pressing process on the transparent conductive film.

[0031] The above S3 is to reduce the surface roughness of the Ag-NW transparent motor by low-pressure mechanical pressing, specifically, as Figure 1 As shown in (c), a pressure piece is placed on the transparent conductive film with the semi-cured adhesive layer as the base prepared in S2 to apply a pressure of 0.4N.

[0032] It is conceivable that the pressure piece may be selected from an object with a flat and smooth surface such as a glass plate or a steel plate.

[0033] S4: performing a second heating treatment on the transparent conductive film after the pressing treatment to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0034] The above S4 is the complete curing of the semi-cured adhesive layer. Specifically, the transparent conductive film obtained in S3 is placed in a heating device and heated at 70° C. for 4 h to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0035] It is contemplated that the heating device may be selected from an oven or a hot plate.

[0036] After low-pressure mechanical pressing and complete curing treatment, the adhesion of the Ag-NW transparent conductive film is further improved and the surface roughness is further reduced.

[0037] Figure 1 The difference between this application and the prior art is shown. Figure 1 (a) shows the preparation process of PET / AgNW transparent conductive film. Figure 1 (b) shows the preparation process of PET / S-PDMS / AgNW transparent conductive film. Figure 1 (c) shows the preparation process of P-PET / S-PDMS / AgNW transparent conductive film.

[0038] Figure 2 (a) shows the effect of liquid bonding layer on the Ag-NW contact resistance. Figure 2(b) shows the effect of the semi-cured PDMS adhesive layer on the Ag-NW contact resistance. The lack of fluidity reduces the probability of PDMS flowing into the contact points between nanowires (NW-NW) during the embedding process of AgNW. Compared with the traditional embedding scheme, the semi-cured adhesive layer improves the adhesion between AgNW and the substrate, reduces the surface roughness, and gives the Ag-NW transparent conductive film excellent optoelectronic properties.

[0039] Figure 3 The comparison of the effects of liquid and semi-cured PDMS adhesive layers on the optoelectronic properties of Ag-NW transparent conductive films is shown, where: Figure 3 (a) shows the surface resistance comparison of Ag-NW transparent conductive films based on PET, semi-cured PDMS and liquid PDMS bonding layers while maintaining a transmittance of 90%. Compared with PET / AgNW transparent conductive film, the surface resistance of PET / S-PDMS / AgNW transparent conductive film has almost no change, while the surface resistance of PET / L-PDMS / AgNW transparent conductive film increases sharply. Figure 3 (b) Demonstrates the conductivity of Ag-NW transparent conductive film on PET and semi-cured PDMS bonding layer substrate at different transmittances. Figure 3 This indicates that the semi-cured PDMS adhesive layer not only has no negative impact on the conductivity of the transparent conductive film, but also has no effect on its transmittance.

[0040] Figure 4 The evaluation of the adhesion of Ag-NW transparent conductive films is shown, where Figure 4 (a) shows the change of AgNW density on the surface of the bonding layer between PET and semi-cured PDMS under different scratching pressures. Within the test range, when the scratching pressure of PET / AgNW transparent conductive film is 3N, some AgNW on the substrate surface has fallen off. When the scratching pressure increases to 5N, the residual amount of AgNW on the substrate surface is less than 50% compared with the initial amount. On the contrary, even if the scratching pressure increases to 5N, the AgNW distributed on the surface of the PET / S-PDMS substrate only shows a slightly disordered morphology, and the amount of AgNW attached to the substrate surface has almost no change compared with the initial amount. Figure 4 (b) shows the change of the surface resistance of the Ag-NW transparent conductive film based on PET under different scratching pressures. Figure 4(b) shows the change in the surface resistance of the Ag-NW transparent conductive film with a semi-cured PDMS adhesive layer as the substrate under different scratching pressures, especially the specific performance under a scratching pressure of 2N. When the scratching pressure exceeds 3N, the AgNW attached to the surface of the PET substrate begins to fall off, causing the surface resistance of the PET / AgNW transparent conductive film to increase. When the scratching pressure is 6N, its surface resistance can no longer be detected and it has no conductivity. On the contrary, even under a scratching pressure of 6N, the change in the surface resistance of the PET / S-PDMS / AgNW transparent conductive film only increases by 0.23 times.

[0041] Furthermore, the surfaces of the PET / AgNW and PET / S-PDMS / AgNW transparent conductive films were repeatedly scratched with a pressure of 2N. Figure 4 As shown in (c), after more than 15 scratches, the surface resistance of the PET / AgNW transparent conductive film could no longer be detected, indicating that it was not conductive. However, even after 30 scratches, the change in the surface resistance of the PET / S-PDMS / AgNW transparent conductive film only increased by 0.27 times, indicating that the semi-cured PDMS adhesive layer significantly improved the adhesion between the AgNW and the substrate, making the Ag-NW transparent conductive film have excellent scratch resistance.

[0042] Figure 5 Figure 4 shows the AFM characterization of the surface roughness of the Ag-NW transparent conductive film, where Figure 5 (a) shows the AFM characterization of the Ag-NW transparent conductive film combined with semi-cured and low-pressure mechanical pressed PDMS bonding layer, Figure 5 (b) shows the AFM characterization of the Ag-NW transparent conductive film with semi-cured PDMS bonding layer. Figure 5 (c) shows the AFM characterization of the Ag-NW transparent conductive film based on PET. The surface roughness of the PET / AgNW transparent conductive film (RMS=108nm) is significantly greater than that of the PET / S-PDMS / AgNW transparent conductive film (RMS=59.4nm), while the surface roughness of the P-PET / S-PDMS / AgNW transparent conductive film is further reduced to 29.5nm; these results show that the combination of semi-curing and low-pressure mechanical pressing method has successfully prepared Ag-NW transparent conductive films with high adhesion and low surface roughness.

[0043] Figure 6 The evaluation of the mechanical flexibility of AgN transparent conductive films is shown, where Figure 6 (a) Figure 6(b) Shows the changes in the surface resistance of the Ag-NW transparent conductive film based on PET, the surface resistance of the Ag-NW transparent conductive film based on the semi-cured PDMS adhesive layer, and the surface resistance of the Ag-NW transparent conductive film based on the PDMS adhesive layer combined with semi-curing and low-pressure mechanical pressing as a function of different bending radii and torsion angles; at the same bending radius and torsion angle, the increase in the surface resistance of the PET / AgNW transparent conductive film exceeded 10%, while the surface resistance of the PET / S-PDMS / AgNW and P-PET / S-PDMS / AgNW transparent conductive films only increased by less than 4%; these studies show that the preparation method combining semi-curing and low-pressure mechanical pressing not only gives the AgNW transparent conductive film high adhesion, low surface roughness and excellent optoelectronic properties, but also has excellent mechanical flexibility.

[0044] Example 2 This embodiment provides a method for preparing a Ag-NW transparent conductive film with high adhesion and low surface roughness by combining semi-curing and low-pressure mechanical pressing, including the following preparation steps: S1: 250 μL of a mixed solution of a polymer and a cross-linking agent was coated on the surface of a polyethylene terephthalate (PET) substrate, and heated at 70° C. for 4 minutes to obtain a semi-cured adhesive layer based on PET.

[0045] The above S1 is a preparation step of a semi-cured bonding layer. Specifically, the polymer can be polydimethylsiloxane (PDMS), and the PDMS and the cross-linking agent are mixed in a ratio of 10:1 to obtain a PDMS solution. 250 μL of the PDMS solution is taken, and the coating method can be spin coating. The 250 μL PDMS solution is spin-coated on the surface of the PET substrate at 1000 r / min for 30 seconds, and the substrate is heated at 70°C for 4 min to obtain a semi-cured bonding layer with PET as the base.

[0046] It is conceivable that the polymer may also be selected from vinyl alcohol, chitosan or sodium alginate.

[0047] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0048] S2: coating 100 μL of a silver nanowire (AgNW) dispersion having a concentration of 0.2 mg / mL on the surface of the semi-cured adhesive layer, and obtaining a transparent conductive film with the semi-cured adhesive layer as a base after drying; The above S2 is the coating of AgNW transparent conductive film. Specifically, the solvent of AgNW dispersion can be ethanol. 100 μL of AgNW ethanol dispersion with a concentration of 0.2 mg / mL is coated on the semi-cured adhesive layer prepared in S1 four times and then allowed to dry naturally.

[0049] It is conceivable that the solvent of the AgNW dispersion may also be water or propanol.

[0050] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0051] S3: placing a pressure piece on the transparent conductive film to perform a pressing process on the transparent conductive film.

[0052] The above S3 is to use low-pressure mechanical pressing to reduce the surface roughness of the Ag-NW transparent motor. Specifically, a pressure piece is placed on the transparent conductive film with the semi-cured adhesive layer as the base prepared in S2 to apply a pressure of 0.5N.

[0053] It is conceivable that the pressure piece may be selected from an object with a flat and smooth surface such as a glass plate or a steel plate.

[0054] S4: performing a second heating treatment on the transparent conductive film after the pressing treatment to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0055] The above S4 is the complete curing of the semi-cured adhesive layer. Specifically, the transparent conductive film obtained in S3 is placed in a heating device and heated at 70° C. for 4 h to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0056] It is contemplated that the heating device may be selected from an oven or a hot plate.

[0057] Example 3 This embodiment provides a method for preparing a Ag-NW transparent conductive film with high adhesion and low surface roughness by combining semi-curing and low-pressure mechanical pressing, including the following preparation steps: S1: 200 μL of a mixed solution of a polymer and a cross-linking agent was coated on the surface of a polyethylene terephthalate (PET) substrate, and heated at 72° C. for 5 minutes to obtain a semi-cured adhesive layer based on PET.

[0058] The above S1 is a preparation step of a semi-cured bonding layer. Specifically, the polymer can be polydimethylsiloxane (PDMS), and the PDMS and the cross-linking agent are mixed in a ratio of 10:1 to obtain a PDMS solution. 200 μL of the PDMS solution is taken, and the coating method can be spin coating. The 200 μL PDMS solution is spin-coated on the surface of the PET substrate at 1000 r / min for 30 seconds, and the substrate is heated at 72°C for 5 min to obtain a semi-cured bonding layer with PET as the base.

[0059] It is conceivable that the polymer may also be selected from vinyl alcohol, chitosan or sodium alginate.

[0060] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0061] S2: coating 300 μL of a silver nanowire (AgNW) dispersion having a concentration of 0.8 mg / mL on the surface of the semi-cured adhesive layer, and obtaining a transparent conductive film with the semi-cured adhesive layer as a base after drying; The above S2 is the coating of AgNW transparent conductive film. Specifically, the solvent of AgNW dispersion can be ethanol. 100 μL of AgNW ethanol dispersion with a concentration of 0.8 mg / mL is coated on the semi-cured adhesive layer prepared in S1 four times and then allowed to dry naturally.

[0062] It is conceivable that the solvent of the AgNW dispersion may also be water or propanol.

[0063] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0064] S3: placing a pressure piece on the transparent conductive film to perform a pressing process on the transparent conductive film.

[0065] The above S3 is to use low-pressure mechanical pressing to reduce the surface roughness of the Ag-NW transparent motor. Specifically, a pressure piece is placed on the transparent conductive film with the semi-cured adhesive layer as the base prepared in S2 to apply a pressure of 0.4N.

[0066] It is conceivable that the pressure piece may be selected from an object with a flat and smooth surface such as a glass plate or a steel plate.

[0067] S4: performing a second heating treatment on the transparent conductive film after the pressing treatment to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0068] The above S4 is the complete curing of the semi-cured adhesive layer. Specifically, the transparent conductive film obtained in S3 is placed in a heating device and heated at 70° C. for 4 h to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0069] It is contemplated that the heating device may be selected from an oven or a hot plate.

[0070] Example 4 This embodiment provides a method for preparing a Ag-NW transparent conductive film with high adhesion and low surface roughness by combining semi-curing and low-pressure mechanical pressing, including the following preparation steps: S1: 300 μL of a mixed solution of a polymer and a cross-linking agent was coated on the surface of a polyethylene terephthalate (PET) substrate, and heated at 72° C. for 4 minutes to obtain a semi-cured adhesive layer based on PET.

[0071] The above S1 is a preparation step of a semi-cured bonding layer. Specifically, the polymer can be polydimethylsiloxane (PDMS), and the PDMS and the cross-linking agent are mixed in a ratio of 10:1 to obtain a PDMS solution. 300 μL of the PDMS solution is taken, and the coating method can be spin coating. The 300 μL PDMS solution is spin-coated on the surface of the PET substrate at 1000 r / min for 30 seconds, and the substrate is heated at 72°C for 4 min to obtain a semi-cured bonding layer with PET as the base.

[0072] It is conceivable that the polymer may also be selected from vinyl alcohol, chitosan or sodium alginate.

[0073] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0074] S2: coating 500 μL of a silver nanowire (AgNW) dispersion having a concentration of 0.8 mg / mL on the surface of the semi-cured adhesive layer, and obtaining a transparent conductive film with the semi-cured adhesive layer as a base after drying; The above S2 is the coating of AgNW transparent conductive film. Specifically, the solvent of AgNW dispersion can be ethanol. 500 μL of AgNW ethanol dispersion with a concentration of 0.8 mg / mL is coated on the semi-cured adhesive layer prepared in S1 four times and then allowed to dry naturally.

[0075] It is conceivable that the solvent of the AgNW dispersion may also be water or propanol.

[0076] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0077] S3: placing a pressure piece on the transparent conductive film to perform a pressing process on the transparent conductive film.

[0078] The above S3 is to use low-pressure mechanical pressing to reduce the surface roughness of the Ag-NW transparent motor. Specifically, a pressure piece is placed on the transparent conductive film with the semi-cured adhesive layer as the base prepared in S2 to apply a pressure of 0.6N.

[0079] It is conceivable that the pressure piece may be selected from an object with a flat and smooth surface such as a glass plate or a steel plate.

[0080] S4: performing a second heating treatment on the transparent conductive film after the pressing treatment to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0081] The above S4 is the complete curing of the semi-cured adhesive layer. Specifically, the transparent conductive film obtained in S3 is placed in a heating device and heated at 70° C. for 4 h to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0082] It is contemplated that the heating device may be selected from an oven or a hot plate.

[0083] Example 5 This embodiment provides a method for preparing a Ag-NW transparent conductive film with high adhesion and low surface roughness by combining semi-curing and low-pressure mechanical pressing, including the following preparation steps: S1: 300 μL of a mixed solution of a polymer and a cross-linking agent was coated on the surface of a polyethylene terephthalate (PET) substrate, and heated at 75° C. for 5 minutes to obtain a semi-cured adhesive layer based on PET.

[0084] The above S1 is a preparation step of a semi-cured bonding layer. Specifically, the polymer can be polydimethylsiloxane (PDMS), and the PDMS and the cross-linking agent are mixed in a ratio of 10:1 to obtain a PDMS solution. 300 μL of the PDMS solution is taken, and the coating method can be spin coating. The 300 μL PDMS solution is spin-coated on the surface of the PET substrate at 1000 r / min for 30 seconds, and the substrate is heated at 75°C for 5 min to obtain a semi-cured bonding layer with PET as the base.

[0085] It is conceivable that the polymer may also be selected from vinyl alcohol, chitosan or sodium alginate.

[0086] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0087] S2: coating 1000 μL of a silver nanowire (AgNW) dispersion having a concentration of 1.0 mg / mL on the surface of the semi-cured adhesive layer, and obtaining a transparent conductive film with the semi-cured adhesive layer as a substrate after drying; The above S2 is the coating of AgNW transparent conductive film. Specifically, the solvent of AgNW dispersion can be ethanol. 1000 μL of AgNW ethanol dispersion with a concentration of 1.0 mg / mL is coated on the semi-cured adhesive layer prepared in S1 four times and then allowed to dry naturally.

[0088] It is conceivable that the solvent of the AgNW dispersion may also be water or propanol.

[0089] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0090] S3: placing a pressure piece on the transparent conductive film to perform a pressing process on the transparent conductive film.

[0091] The above S3 is to use low-pressure mechanical pressing to reduce the surface roughness of the Ag-NW transparent motor. Specifically, a pressure piece is placed on the transparent conductive film with the semi-cured adhesive layer as the base prepared in S2 to apply a pressure of 0.6N.

[0092] It is conceivable that the pressure piece may be selected from an object with a flat and smooth surface such as a glass plate or a steel plate.

[0093] S4: performing a second heating treatment on the transparent conductive film after the pressing treatment to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0094] The above S4 is the complete curing of the semi-cured adhesive layer. Specifically, the transparent conductive film obtained in S3 is placed in a heating device and heated at 70° C. for 4 h to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0095] It is contemplated that the heating device may be selected from an oven or a hot plate.

[0096] Example 6 This embodiment provides a method for preparing a Ag-NW transparent conductive film with high adhesion and low surface roughness by combining semi-curing and low-pressure mechanical pressing, including the following preparation steps: S1: 300 μL of a mixed solution of a polymer and a cross-linking agent was coated on the surface of a polyethylene terephthalate (PET) substrate, and heated at 75° C. for 4 minutes to obtain a semi-cured adhesive layer based on PET.

[0097] The above S1 is a preparation step of a semi-cured bonding layer. Specifically, the polymer can be polydimethylsiloxane (PDMS), and the PDMS and the cross-linking agent are mixed in a ratio of 10:1 to obtain a PDMS solution. 300 μL of the PDMS solution is taken, and the coating method can be spin coating. The 300 μL PDMS solution is spin-coated on the surface of the PET substrate at 1000 r / min for 30 seconds, and the substrate is heated at 75°C for 4 min to obtain a semi-cured bonding layer with PET as the base.

[0098] It is conceivable that the polymer may also be selected from vinyl alcohol, chitosan or sodium alginate.

[0099] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0100] S2: coating 1000 μL of a silver nanowire (AgNW) dispersion having a concentration of 1.0 mg / mL on the surface of the semi-cured adhesive layer, and obtaining a transparent conductive film with the semi-cured adhesive layer as a substrate after drying; The above S2 is the coating of AgNW transparent conductive film. Specifically, the solvent of AgNW dispersion can be ethanol. 1000 μL of AgNW ethanol dispersion with a concentration of 1.0 mg / mL is coated on the semi-cured adhesive layer prepared in S1 four times and then allowed to dry naturally.

[0101] It is conceivable that the solvent of the AgNW dispersion may also be water or propanol.

[0102] It is conceivable that the coating method can also be selected as Meyer rod coating or extrusion coating.

[0103] S3: placing a pressure piece on the transparent conductive film to perform a pressing process on the transparent conductive film.

[0104] The above S3 is to use low-pressure mechanical pressing to reduce the surface roughness of the Ag-NW transparent motor. Specifically, a pressure piece is placed on the transparent conductive film with the semi-cured adhesive layer as the base prepared in S2 to apply a pressure of 0.6N.

[0105] It is conceivable that the pressure piece may be selected from an object with a flat and smooth surface such as a glass plate or a steel plate.

[0106] S4: performing a second heating treatment on the transparent conductive film after the pressing treatment to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0107] The above S4 is the complete curing of the semi-cured adhesive layer. Specifically, the transparent conductive film obtained in S3 is placed in a heating device and heated at 70° C. for 4 h to obtain a transparent conductive film with the completely cured adhesive layer as the base.

[0108] It is contemplated that the heating device may be selected from an oven or a hot plate.

[0109] Several embodiments of the present invention have been described, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the invention. These embodiments and their variations are included in the scope and spirit of the invention, and are also included in the invention described in the claims and their equivalents.

Claims

1. A method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing, characterized in that: include: 200-300 μL of a mixed solution of a polymer and a crosslinking agent is coated on the surface of a polyethylene terephthalate substrate, and a semi-cured adhesive layer based on PET is obtained after a first heating treatment; Applying 100-1000 μL of a silver nanowire dispersion with a concentration of 0.2-1.0 mg / mL on the surface of the semi-cured adhesive layer, and obtaining a transparent conductive film with the semi-cured adhesive layer as a base after drying; placing a pressure piece on the transparent conductive film to perform a pressing process on the transparent conductive film; The transparent conductive film after the pressing process is subjected to a second heating process to obtain a transparent conductive film with the completely cured adhesive layer as a base.

2. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 1, characterized in that: The polymer is one of polydimethylsiloxane, polyvinyl alcohol, chitosan or sodium alginate.

3. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 1, characterized in that: The mixed solution comprises: The polymer and crosslinker were mixed in a ratio of 10:

1.

4. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 1, characterized in that: The mixed solution is coated on the surface of the PET substrate including: The coating method is one of spin coating, Meyer rod coating or extrusion coating.

5. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 4, characterized in that: The spin coating comprises: The speed was set to 1000 r / min and the time was set to 30 seconds.

6. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 1, characterized in that: Coating the AgNW dispersion on the surface of the semi-cured bonding layer comprises: The coating method is one of spin coating, Meyer rod coating or extrusion coating.

7. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 1, characterized in that: The first heating process comprises: The heating temperature was set to 70°C and the heating time was set to 5 minutes.

8. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 1, characterized in that: The solvent of the AgNW dispersion is one of ethanol, water or propanol.

9. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 1, characterized in that: The pressing process comprises: The pressing pressure was set to 0.4 N-0.6 N.

10. The method for preparing a silver nanowire transparent conductive film by combining semi-curing and low-pressure pressing according to claim 1, characterized in that: The second heating process comprises: The heating temperature was set to 70°C and the heating time was set to 4 hours.

Citation Information

Patent Citations

  • Substrate film for transparent electrode film production

    CN103958193A

  • High-bending-resistance transparent conducting film and making method thereof

    CN104766646A

  • Method for manufacturing flexible transparent conductive film based on low-voltage driving liquid film embedded electrospray 3D printing

    CN112509747A

  • Base material with transparent conductive film, and manufacturing method thereof

    JP2011198642A

  • Method for manufacturing silver nanowire transparent electrode, and silver nanowire transparent electrode manufactured thereby

    WO2020101289A1